A crosslinkable graphene oxide in waterborne polyurethane anticorrosive coatings: Experiments and simulation. (1st May 2020) - Cui, Jincan; Xu, Jingcheng; Li, Jing; Qiu, Hanxun; Zheng, Shiyou; Yang, Junhe
Abstract: A crosslinkable graphene oxide (GO) was synthesized and employed as reinforcement in waterborne polyurethane (WPU) composite coatings for improving corrosion protection properties. Polycarbodiimide (PCD), a crosslinking agent of WPU, was chosen to modify GO. Three different conformations of functionalized graphene will be generated: grape cluster conformation, network conformation and tail conformation, varying mainly with the PCD/GO ratio. Experiments and molecular dynamics simulation were carried out to study the correlations between the PCD/GO ratio, the conformations of functionalized graphene, as well as the dispersion state of graphene layers. The functionalized graphene with tail conformation was crosslinkable with WPU molecules along the interfaces. Electrochemical impedance spectroscopy showed that the WPU coatings with 0.2 wt% crosslinkable graphene remained at a maximum impedance modulus of 10 9  Ω cm 2 after 120 days immersion without any decrease. The superior anticorrosive properties benefited from the barrier properties of well-dispersed graphene layers, the crosslinking structure along the functionalized graphene/WPU interfaces, as well as the improved water resistance of the coatings. Graphical abstract: Image 1 Highlights: Graphene oxide was functionalized by polycarbodiimide, which was crosslinkable with waterborne polyurethane. Quantitative analysis on dispersion state of graphene sheets was carried out by molecular dynamics simulation. The correlations between functionalization parameters and dispersion state of graphene sheets were revealed. The impedance modulus of the composite coatings was barely decreased for 120 days. The well-dispersed graphene sheets and the water resistance along the composite interface benefited the corrosion resistance.